Analysis of the Historical and Legal Trajectory of Education for Students with High Abilities/Giftedness - HA/G (Interdisciplinary Studies Journal, 2024)
People with giftedness have high potential in different areas of knowledge compared to the rest of the population. Public policies in Brazil aimed at the highly gifted have been in place for about a century, considering the first publications. However, it was only in LDB 5692/71 that these students were officially mentioned at national level. In order to answer the question: in which laws, decrees and initiatives that deal with Special Education in Brazil, starting with the current LDB (9394/96), are public policies guaranteed for AH/SD? And with the general objective of analyzing Brazilian educational legislation, starting with the current LDB (9394/96) with regard to public policies for serving students with HS/G, the text makes a chronology starting from the Law of Guidelines and Bases (LDB 9394/96) going through public and private regulations and initiatives that brought and bring contributions to serving this public until the year 2023, with the promulgation of CNE/CP Opinion No.: 51/2023 that specifies the steps of serving students with HS/G. The documentary research, with a qualitative approach, concluded that there are laws and guiding documents in Brazil that make reference to guaranteeing care for students with ASD/SD, but the enrollment figures in the School Census show that these regulations have not been implemented.
Keywords: Educational Legislation; Public Policies; Identification; High Abilities; Giftedness